Genetic and Biochemical Diversity among Valeriana jatamansi Populations from Himachal Pradesh - Sunil Kumar Singh; Rajan Katoch; Rakesh Kumar Kapila (The Scientific World Journal)
Valeriana jatamansi Jones is an important medicinal plant that grows wild in Himachal Pradesh, India. Molecular and biochemical diversity among 13 natural populations from Himachal Pradesh was assessed using RAPD and GC-MS to know the extent of existing variation. A total of seven genetically diverse groups have been identified based on RAPD analysis which corroborated well with the analysis based on chemical constituents. The essential oil yield ranged from 0.6% to 1.66% (v/w). A negative correlation between patchouli alcohol and viridiflorol, the two major valued constituents, limits the scope of their simultaneous improvement. However, other few populations like Chamba-II and Kandi-I were found promising for viridiflorol and patchouli alcohol, respectively. The analysis of chemical constitution of oil of the populations from a specific region revealed predominance of specific constituents indicating possibility of their collection/selection for specific end uses like phytomedicines. The prevalence of genetically diverse groups along with sufficient chemical diversity in a defined region clearly indicates the role of ecology in the maintenance of evolution of this species. Sufficient molecular and biochemical diversity detected among natural populations of this species will form basis for the future improvement.